An Analytical and Experimental Investigation of GFRP Reinforced Concrete Deep Beams - Saraswathi, Gurram; Bhoomesh, S.; Sudharshan Reddy, B. (Journal of Neonatal Surgery, 2025)
Today's civil construction sector faces a major challenge in the form of steel corrosion in reinforced concrete structures, which significantly reduces the structures' lifespan. Numerous approaches have been investigated to overcome this problem, and Fiber Reinforced Polymer (FRP) materials have emerged as a viable substitute because of their low weight-to-strength ratio and anti-corrosive qualities. The flexural and shear behavior of FRP reinforced thin concrete beams has been extensively studied, whereas deep reinforced concrete (RC) beams reinforced with FRP rebars have received less attention. The purpose of this study is to examine how deep beams reinforced with Glass Fiber Reinforced Polymer (GFRP) web reinforcement behave under shear. Since commercially produced FRP reinforcements that suited the necessary standards were not readily available, GFRP reinforcement bars and stirrups were made utilizing a process known as "Manual Fiber-Trusion". Tensile strength can be increased by using this technique to fabricate GFRP reinforcement in the required sizes and shapes with a certain fiber volume and resin content. In contrast to flexural failure, shear failure is more likely to occur in deep beams, which are defined by a depth equal to their span. Thirteen concrete deep beams with various GFRP web reinforcement designs were examined, with certain parameters held constant, including the "shear span to depth" ratio and the percentage of web reinforcement. The findings of two series of experiments show that deep beams reinforced with GFRP web reinforcement have a much higher ultimate shear load carrying capacity than those without. Analytical "Strut-and Tie" models were also used for comparison, and the results were marginally better than the experimental ones. Based on these findings, recommendations were made to amend the ACI 318-08 code to allow for GFRP-reinforced concrete deep beams with reduced shear span to depth ratios. In the end, a design equation that predicted the shear bearing capacity of deep beams reinforced with GFRP web produced results that were satisfactory. For such beams with small shear span to depth ratios, this equation provides a useful tool for estimating shear load capacity..